Quantitative Determination of Umbelliferone in the Root Extract of Cichorium intybus by HPTLC - Rajkumari; Ali, M.; Vidhu, Aeri (Asian Journal of Chemistry, 2010)
A simple sensitive HPTLC method developed for determination of umbelliferone in the methanolic root extract of Cichorium intybus by HPTLC. The stationary phase was precoated silica gel 60 F254 and the mobile phase used was toluene:ethyl acetate:glacial acetic acid (8:13:1 v/v/v). The plate was scanned and quantified at 356 nm for umbelliferone. The method was validated in terms of linearity, accuracy and specificity. The proposed HPTLC method provides a faster and cost effective control for routine analysis of umbelliferone in the extracts containing Cichorium intybus coumarins.